Nestin expression throughout multistep pathogenesis of multiple myeloma - Svachova, Hana; Kryukov, Fedor; Kryukova, Elena; Sevcikova, Sabina; Nemec, Pavel; Greslikova, Henrieta; Rihova, Lucie; Kubiczkova, Lenka; Hajek, Roman (British journal of haematology, 2014)
The stem cell marker nestin (NES) is found in dividing cells of developing and regenerating tissues. Upon terminal differentiation, NES expression is diminished but may be re-expressed following injury or in cancer. Surprisingly, we recently confirmed NES as a tumour-specific marker for mature CD138(+) 38(+) plasma cells (PC) in multiple myeloma (MM). The present study analysed NES expression throughout the spectrum of MM developmental stages, starting with individuals with no haematological malignancy, through monoclonal gammopathy of undetermined significance (MGUS) and MM to plasma cell leukaemia (PCL) and MM cell lines. NES was analysed in bone marrow PC of 163 MM, four PCL and nine MGUS patients, 10 individuals with no haematological malignancy and 6 myeloma cell lines (OPM-2, RPMI-8226, MOLP-8, U-266, EJM, NCI-H929) by flow cytometry and/or real-time polymerase chain reaction or immunochemistry. We observed a tendency of increased NES expression in parallel with disease progression. NES was evaluated as a reliable marker for accurate discrimination between MM patients and the control group. High NES levels were strongly associated with the presence of 1q21 gain. For the first time, NES was demonstrated to predict worse response to conventional therapy/novel agents. These results suggest that NES might become a useful clinical parameter with an important role in MM pathogenesis.
Keywords: Prognosis; flow cytometry; nádorové buňky kultivované; recidiva; Adult; senioři; Neoplasm Staging; Aged; Male; stem cells; progrese nemoci; RNA nádorová; RNA, Messenger; monoklonální gamapatie nejasného významu; lidé; lidé středního věku; Humans; Multiple Myeloma; nestin; Middle Aged; Biomarkers, Tumor; nádorové biomarkery; plazmocelulární leukemie; nádorové proteiny; imunofenotypizace; senioři nad 80 let; Aged, 80 and over; monoclonal gammopathy; mnohočetný myelom; mužské pohlaví; RNA, Neoplasm; staging nádorů; dospělí; Monoclonal Gammopathy of Undetermined Significance; Recurrence; Nestin; multiple myeloma; messenger RNA; Disease Progression; ženské pohlaví; Tumor Cells, Cultured; Female; Immunophenotyping; prognóza; Neoplasm Proteins; Leukemia, Plasma Cell